Entrepreneurial industrial design: asserting projectual autonomy beyond neoliberal logics - D'Amico, Enrique (2025)
Entrepreneurship in industrial design entails the convergence and conflict of two distinct cultural logics: that of design and that of business. This self-organized mode of professional practice, increasingly prevalent in contemporary life, is shaped by a dominant ideological infrastructure rooted in global centers, which promotes so-called “success stories” based on economic performance. Such narratives often marginalize alternative practices and influence designers’ professional expectations, limiting the imagination of divergent or locally rooted trajectories. This article, derived from doctoral research, explores alternative ways of understanding entrepreneurship in design by analyzing the discursive cultures adopted by industrial designers and how they reinterpret entrepreneurial activity in specific territorial contexts. The study is grounded in a multiple case analysis of eight entrepreneurial initiatives developed between 2009 and 2019 by graduates of the Faculty of Arts at the National University of La Plata, within the Buenos Aires Entrepreneurial Ecosystem (EEB). Methodologically, the research adopts a qualitative approach, using semi-structured interviews with designers and key informants. It is framed by an integrated analytical model that considers three interrelated dimensions: the designer-entrepreneur, the enterprise, and the ecosystem in which it unfolds. Through this lens, the study reconstructs entrepreneurial trajectories and examines how designers negotiate the intersection of professional identity, local context, and personal life projects. The findings highlight the ways in which designers articulate critical forms of self-organization, resisting hegemonic market logics and pursuing what the study terms projectual sovereignty—an autonomous and context-sensitive way of designing and living.